Analysis of the Development of Online Loans and Gen Z Opinions in Makassar City in the Era of Digital Capitalism - Sugianto, Sugianto; Hasriani, Hasriani; Islami, Muhammad Mitsal; Noor, Randi Mauna (Journal La Bisecoman, 2025)
In its development, online loans have become the choice of many people to meet their needs. This is due to the ease and speed of the process. However, this gives rise to new problems, namely the large number of online loan services that are not registered or illegal, so that their existence is very detrimental to people who make loans, because the loans are carried out by providing unreasonable interest charges. Carrying out a descriptive economic analysis of the development of crime which occurred due to illegal lending in Makassar City in 2023-2024, Analyzing the factors that influence GEN Z to take online loans. The method used in this research is quantitative and qualitative research or what is usually called Mix Method. The results of this research are that the growth of online loan companies is increasing every year, but for those registered with the OJK it is decreasing, the development of online loan crime is increasing rapidly, this can be seen from the number of complaints to the OJK and the news circulating, Lifestyle factors have no significant influence on loans. Online, the Need Factor has a positive and significant effect on Online Loans, Access to Financial Institutions has a positive and significant effect on Online Loans. research.